30-minute social media marketing : step-by-step techniques to spread the word about your business fast and free - Gunelius, Susan (McGraw Hill, 2011)
Small business marketing expert Susan Gunelius guides readers through social media marketing for small business, providing measurable results in just 30 minutes a day